Network Education Sekolah Dasar Islam Mohammad Hatta Kota Malang - Kukuh Yudhistiro; Sumartono Sumartono Sumartono; Dwi Arman Prasetya; Bambang Nurdewanto Nurdewanto; Elta Sonalitha Sonalitha (JAPI (Jurnal Akses Pengabdian Indonesia), 2019)
Various methods can be done to improve teacher performance in the implementation of the teaching and learning process. One form of improvement in teacher performance carried out in this service is the use of laboratories and computer networks to optimize methods of evaluating students through the creation of question banks stored on school servers, creating class name lists that can include a variety of student information including automated assessment demographic information for Computer Answer Sheet (LJK) tests using scanners, use of Local Area Network and internet based tests, processing of Local Area Network (LAN) and internet automated test scores and producing reporting such as analysis of test items, skill reports. In addition, this service also provides asset management training to computer laboratory officers. This service was trained for the teacher of Islamic Primary School Mohammad Hatta, Malang City. The results of this service have had an effective impact on improving the quality of the exam content and the performance of the teacher in carrying out the recapitulation and management of the asset repository of computer laboratories at SDI Mohammad Hatta.